1987
DOI: 10.1007/bf00043953
|View full text |Cite
|
Sign up to set email alerts
|

7. The role of plant growth regulators in forest tree cambial growth

Abstract: The regulation of cell-division activity in the vascular cambium and of secondary xylem and phloem development is reviewed for temperate-zone tree species in relation to auxins, gibberellins, abscisic acid, cytokinins, and ethylene . Representatives of the first four of these PGR classes (IAA,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(9 citation statements)
references
References 180 publications
(190 reference statements)
1
8
0
Order By: Relevance
“…Cambial meristematic activity, shorter enlarging time of tracheid and the number of wall layers produced [58,80] may have played a more important role. A reduction in crown growth or LAI during drought could signal a reduction in cambial growth via lower indole-3-acetic acid (IAA) production [10]. Given future climate change scenarios, we could anticipate a continued coexistence of both species at this site and region under current levels of drought stress with a competition advantage for P. nigra given its faster growth and more flexible xylem development.…”
Section: Intrinsic Water-use Efficiencymentioning
confidence: 99%
“…Cambial meristematic activity, shorter enlarging time of tracheid and the number of wall layers produced [58,80] may have played a more important role. A reduction in crown growth or LAI during drought could signal a reduction in cambial growth via lower indole-3-acetic acid (IAA) production [10]. Given future climate change scenarios, we could anticipate a continued coexistence of both species at this site and region under current levels of drought stress with a competition advantage for P. nigra given its faster growth and more flexible xylem development.…”
Section: Intrinsic Water-use Efficiencymentioning
confidence: 99%
“…Earlier studies had shown that indole-3-acetic acid (IAA) plays an important role in cambial activity and wood formation of woody plants [11,12]. Since then, numerous experiments using exogenous auxin treatments of both hardwoods and conifers have demonstrated the potential of IAA to affect most aspects of cambial growth in a dose-dependent manner, including xylem and phloem production and size, as well as secondary wall thickness of xylem elements [13,14,15,16]. Gibberellins (GAs) are also important regulators of stem growth and wood formation and considerable evidence demonstrates that exogenous application of gibberellic acid (GA 3 ) promotes cambial cell division, expansion of cambium derivatives and tension wood formation [5,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, latewood (LW) tracheids start forming at times when the intensity of IAA supply to cambium is reduced and the formation of annual shoots has ended. LW tissues have smaller radial dimensions, but thicker cell walls (Little & Savidge 1987), and, forming at the time of reduced IAA concentration, have smaller radial dimensions; on the other hand, they have more time for differentiation and are much more intensely supplied with assimilates from already-formed annual shoots for the creation of their secondary walls, which gives them their typical thick-walled structures (Sundberg et al 1987. According to Larson (1969), the formation of LW occurs when the concentration of IAA is gradually reduced and carbohydrate contents rise.…”
Section: Introductionmentioning
confidence: 99%